How to build a better you with Bryan Dodge - Dodge, Bryan; Dodge Development (Duncanville, Tex : Dodge Development, 2003)
Addresses topics of self-improvement including goal-setting, making life changes, attitude improvement, appreciation of life; accepting life's ebbs and flows, and the importance of continuing education.
DVD.
Not rated.
Presented by Bryan Dodge.
Keywords: Self-actualization (Psychology); Motivation (Psychology); Achievement motivation